Congenital Hydrocephalus and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The frequency of seizures and long-term outcome in 68 children with congenital hydrocephalus not associated with myelomeningocele were examined at the Washington University School of Medicine, St. Louis, MO.